Evaluation of erectile potency and radiation dose to the penile bulb using image guided radiotherapy in the CHHiP trial. (March 2020) - Murray, Julia; Gulliford, Sarah; Griffin, Clare; Wilkins, Anna; Syndikus, Isabel; Staffurth, John; Panades, Miguel; Scrase, Christopher; Parker, Chris; Khoo, Vincent; Dean, Jamie; Mayles, Helen; et al.
Highlights: Dosimetric benefits to the penile bulb was seen in patients treated with IGRT and reduced CTV-PTV margins. Patients who had a lower planned dose to the penile bulb reported less erectile dysfunction. A threshold mean penile bulb dose for erectile dysfunction was determined to around 20 Gy. Abstract: Background and purpose: The penile bulb (PB) dose may be critical in development of post prostate radiotherapy erectile dysfunction (ED). This study aimed to generate PB dose constraints based on dose-volume histograms (DVHs) in patients treated with prostate radiotherapy, and to identify clinical and dosimetric parameters that predict the risk of ED post prostate radiotherapy. Materials and methods: Penile bulb DVHs were generated for 276 patients treated within the randomised IGRT substudy of the multicentre randomised trial, CHHiP. Incidence of ED in relation to dose and randomised IGRT groups were evaluated using Wilcoxon rank sum, Chi-squared test and atlases of complication incidence. Youden index was used to find dose-volume constraints that discriminated for ED. Multivariate analysis (MVA) of effect of dosimetry, clinical and patient-related variables was performed. Results: Reduced treatment margins using IGRT (IGRT-R) produced significantly reduced mean PB dose compared with standard margins (IGRT-S) (median: 25 Gy (IGRT-S) versus 11 Gy (IGRT-R); p < 0.0001). Significant difference in both mean (median: 23 Gy (ED) vs. 18 Gy (no ED); p = 0.011) and maximum (median: 59 Gy (ED) vs. 52 Gy (no ED); p = 0.018) PB doses between those with and without clinician reported ED were identified. Mean PB dose cut-point for ED was derived at around 20 Gy. On MVA, PB mean dose and age predicted for impotence. Conclusion: PB dose appears predictive of post-radiotherapy ED with calculated threshold mean dose of around 20 Gy, substantially lower than published recommendations. IGRT-R enables favourable PB dosimetry and can be recommended provided prostate coverage is not compromised.